Memory and Learning in Plants (Signaling and Communication in Plants, 2018)
This book assembles recent research on memory and learning in plants. Organisms that share a capability to store information about experiences in the past have an actively generated background resource on which they can compare and evaluate coming experiences in order to react faster or even better. This is an essential tool for all adaptation purposes. Such memory/learning skills can be found from bacteria up to fungi, animals and plants, although until recently it had been mentioned only as capabilities of higher animals. With the rise of epigenetics the context dependent marking of experiences on the genetic level is an essential perspective to understand memory and learning in organisms. Plants are highly sensitive organisms that actively compete for environmental resources. They assess their surroundings, estimate how much energy they need for particular goals, and then realize the optimum variant. They take measures to control certain environmental resources. They perceive themselves and can distinguish between 'self' and 'non-self'. They process and evaluate information and then modify their behavior accordingly. The book will guide scientists in further investigations on these skills of plant behavior and on how plants mediate signaling processes between themselves and the environment in memory and learning processes.